Devouring One´s Own Tail Autopoiesis in Perspective - Jehlička, Jakub (Karolinum Press, 2022)
Like the ancient ouroboros devouring its own tail, we are products of our own education, our own rules and methods of cognizing and shaping the world. As such, we are also their victims, living mostly by habit and inherited rules of conduct questioning them only in the moments of crises and sometimes even not then. The purpose of this book is to explore the nature of autopoiesis or the ability of society and its various forms to create, re-create and maintain itself, by putting it in the broader interdisciplinary perspective as having been established within the project itself. The mark of the book is its broad interdisciplinary quality, stretching from philosophy, religious studies and literary theory to new media, linguistics, and political theory.